Genetic variability among Fusarium oxysporum isolates from melon (Cucumis melo) in Qazvin province, Iran - Mahdikhani, Mohammadreza (Horticultural Biotechnology Research, 2016)
Fusarium wilt, caused by Fusarium oxysporum f. sp. melonis (Fom), the soil-borne fungus that can due to more losses in yield of melon plants. Fusarium is a variable fungi in terms of morphology, symptom production, pathogenicity and wide host range. From 2013 to 2015, 120 isolates of F. oxysporum, F. acuminatum, F. graminearum,Â  F. proliferatum and F. solani from melon, were collected from disease suspected plants from the field and defined for pathogenicity in our melon plants. Then, a sort of those were elected for phylogenetic analysis. In the beginning, the Fusarium isolates were classified based on morphology and identifications were authenticated based on sequence data from, EF1Î± and DNA, and then were used to determine whether Fusarium variability is relevant to geographic origin and pathogenicity. Neighbor-joining analyses datasets indicated some clades based on geographic origin but there is not even a single clades including solely of pathogens. Because of the factors affecting in pathogenicity are variable, we should be considered them in future studies. Due to the presence of FOM and some nonpathogenic isolates in almost all clades, it is obvious that Fusarium oxysporum f. sp. melonis is not monophyletic.